Figure 5 from: Shandikov G, Eakin R (2013) Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea. ZooKeys 296: 59-77. https://doi.org/10.3897/zookeys.296.4295 - Shandikov, Gennadiy; Eakin, Richard (Zenodo, 2013)
Figure 5 - Four types of second dorsal fin shape in males of Pogonophryne. See text for explanations. Arrow indicates the point of primary dichotomic branching of anterior longest rays; a type 1: Pogonophryne tronio, holotype, 234 mm SL b type 2: Pogonophryne sp. 208 mm SL c type 3: Pogonophryne neyelovi sp. n., holotype d type 4: Pogonophryne barsukovi, 208 mm SL.